Implementation of human development policy in health sector in decentralization perspective - Genta Rizkyansah; Ety Rahayu (International Journal of Public Health Science (IJPHS), 2021)
The high case of malaria and dengue hemorrhagic fever (DHF) in Indonesia is resolved by government of the Republic of Indonesia through human development policies in health sector. This policy is implemented through the Indonesian health program with family approach. One of the goals of Indonesian health program with family approaches is a disease control. This was descriptive qualitative research to describe the implementation of human development policies in health sector through the Indonesian health program with family approach and to confirm the obstacles in the implementation of intended policy. The results showed that the communication factor is carried out through policy socialization and focus group discussion. The disposition factor is carried out by providing technical support in the form of regulations and intensive provision to health personnel. The bureaucratic structure factor is indicated by the division of tasks and functions of each organization involved. The resource is a factor that becomes an obstacle in policy implementation. Lack of staff and budget are the reasons of program does not run optimally.